A Case of Pulmonary Aspergillosis Presenting Pulmonary Bulla and Eosinophilic Pneumonia - Yamada, Motohiro; Murata, Yoshiharu; Nishi, Kohichi; Fujioka, Masahiko; Nakamura, Yuhichi; Morishita, Daiju; Sasaki, Keiko; Matsuda, Tamotsu; Murakami, Shinya; Yasui, Masahide; Fujimura, Masaki; Muramoto, Shingo (Nihon Kyōbu Shikkan Gakkai zasshi, 1991)
A rare case of a 25-year-old man with pulmonary aspergillosis is reported. Pulmonary bulla and eosinophilic pneumonia in the right upper lobe were diagnosed by chest roentgenogram and trasbronchial lung biopsy. Because the patient developed infective bullae during steroid therapy, we performed transcutaneous thoracic drainage and right upper lobectomy. The resected lung tissue contained numerous hyphae of Aspergillus. Around the hyphae of Aspergillus, granulomatous reatction and eosinophilic infiltration were observed. Antibodies against Aspergillus were detected in the serum of the patient. The number of peripheral blood eosinophils decreased after right upper lobecotmy. These findings suggest that pulmonary bullae and eosinophilic pneumonia may be a rare manifestation of pulmonary aspergillosis.